RETRACTED: Institutional factors of labour potential development in the context of financial support for transformation of social infrastructure - Konorev Aleksandr; Artemov Vladimir; Krivoshlykov Vladimir (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001